Challenges and perspectives of NASICON-type solid electrolytes for all-solid-state lithium batteries - Hou, Minjie; Liang, Feng; Chen, Kunfeng; Dai, Yongnian; Xue, Dongfeng (Nanotechnology, 2020)
NASICON-type (lithium super ionic conductor) solid electrolyte is of great interest because of its high ionic conductivity, wide potential window, and good chemical stability. In this paper, the key problems and challenges of NASICON-type solid electrolyte are described from the aspects of ionic conductivity, electrode interface, and electrochemical stability. Firstly, the migration mechanism of lithium ion is analyzed from the three-dimensional structure of NASICON-type solid electrolyte, and progress in the research of conductivity and stability is summarized. Then, the effective methods to reduce interface impedance and improve the cycle stability of all-solid-state lithium batteries (ASSLBs) with NASICON-type solid electrolyte are introduced. Finally, solutions to improve the conductivity of electrolytes and deal with electrode/electrolyte interface problems are summarized, and the development prospects of ASSLBs are discussed.